Defense Industry Cooperation as an Instrument of Indonesia–Türkiye Defense Diplomacy: A Case Study of the Harimau Medium Tank Joint Development Program - Yunizir Iqbal; Pujo Widodo; Hendra Manurung (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Indonesia’s dependence on foreign defense suppliers has prompted efforts to strengthen domestic defense industrial capabilities through defense diplomacy and international industrial cooperation. This study aimed to analyze how Indonesia–Türkiye defense industrial cooperation contributes to Indonesia’s defense industrial autonomy from a Neo-Realist perspective. Employing a qualitative case study design, data were collected through semi-structured interviews with key stakeholders, document analysis, and examination of relevant policy documents. The findings indicate that Indonesia–Türkiye cooperation extends beyond conventional defense procurement by incorporating technology transfer, joint development, and institutional coordination through the Defense Cooperation Agreement and the Defense Industry Cooperation Meeting. The Harimau Medium Tank program demonstrates that bilateral cooperation has strengthened Indonesia’s defense manufacturing and systems-integration capabilities while reducing strategic dependence on external suppliers. Nevertheless, defense industrial autonomy remains a gradual process because limitations in critical technologies, supporting industrial ecosystems, and human resource capacity continue to constrain domestic capability development. From a Neo-Realist perspective, this cooperation represents an internal balancing strategy through which Indonesia enhances its national defense capabilities while maintaining diversified international partnerships. The study concludes that collaborative defense industrial development can support the long-term pursuit of strategic autonomy, although its effectiveness depends on sustained technology absorption, institutional capacity, and industrial ecosystem development. This study contributes to defense and international relations scholarship by integrating defense diplomacy, defense industrial cooperation, and internal balancing within a unified analytical framework and by providing empirical evidence of how middle powers can pursue strategic autonomy through collaborative capability development.